Phentolamine bioequivalence study - Silva, LFG; Moraes, M. O.; Santana, GSM; Bezerra, FAF; De Nucci, G.; Moraes, MEA (Dustri-verlag Dr Karl Feistle, 2004)
Objective: To assess the bioequivalence of 2 tablet formulations of phentolamine (Regitine phentolamine 40 mg tablet formulation by Novartis, Brazil, as test formulation, and Vasomax, phentolamine 40 mg tablet formulation by Schering Plough S.A., Brazil, as reference formulation). Methods: A single 40 mg oral dose of each formulation was administered to 36 male healthy volunteers. The study was conducted after screening, using an open, randomized, 2-period crossover design, a 7-day interval between doses, and wash-out period of at least 4 weeks. Plasma samples for determination of phentolarnine were obtained predose and at intervals over 720 min postdose. Plasma concentrations were quantified by reversed-phase liquid chromatography coupled to tandem mass spectrometry (LC-MS-MS) with positive ion electrospray ionization using multiple reactions monitoring (MRM) method. Precision of the method was evaluated using calibration curves and plasma quality control samples. The subjects were monitored throughout the study. Systolic and diastolic blood pressure and pulse rate measurement were taken predose and at intervals up to 720 min. Tolerance of both products was good. No serious adverse reactions were reported. The pharmacokinetic parameters calculated for both compounds included: AUC((0-720 min)), AUC((0-infinity)), C-max,C- C-max/AUC((0-720 min),) t(max), t(1/2) and k(c). Results: the maximum concentrations reached (Cmax) were compared. Regitine 40 mg formulation C-max geometric mean ratio was 108.29% (90% Cl = 98.58 - 118.96) of Vasomax 40 mg formulation. The areas under the curve (AUC((0-720 min))) were compared. Regitine 40 formulation (AUC((0-720 min)) geometric mean ratio was 102.33% (90% Cl = 97.21 - 107.72) of Vasomax 40 mg formulation. Conclusion: Since the 90% Cl for both Cmax and AUC ratio where inside the 80 to 125% interval proposed by the Food and Drug Administration, it is concluded that Regitine 40 mg tablet is bioequivalent to Vasomax for the rate and extent of absorption.
Keywords: bioavailability; human; mass spectrometry; pharmacokinetic; phentolamine